2017
DOI: 10.1177/1521025117726520
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Contribute to a Sense of Belonging in Business Students on a Small 4-Year Public Commuter Campus in the Midwest

Abstract: Institutions of higher education are increasingly focused on student outcomes such as persistence. This study investigated factors that contribute to a sense of belonging, a key contributor to persistence, in business students attending a small 4-year public commuter campus in the Midwest. A survey was administered to students in an introductory business course with a first-year experience component to examine three categories of variables: student demographics, faculty interventions, and student activities. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…Students enrolled in the revised GEOL-G 102 laboratories performed better and failed/dropped out less than students during the three previous semesters, suggesting a positive effect on student engagement. There is a well-established relationship between student engagement and academic success (Kuh et al, 2008), and recent work suggests that engagement in the academic setting may be even more important to students on commuter campuses (Whitten, et al, 2017). The dramatic drop in DFW rates in fall 2016 and spring 2017 (4.35% and 4.1% compared with 13% historically) is followed by a comparative increase in fall 2017 (8.3%).…”
Section: Geosciencesmentioning
confidence: 99%
“…Students enrolled in the revised GEOL-G 102 laboratories performed better and failed/dropped out less than students during the three previous semesters, suggesting a positive effect on student engagement. There is a well-established relationship between student engagement and academic success (Kuh et al, 2008), and recent work suggests that engagement in the academic setting may be even more important to students on commuter campuses (Whitten, et al, 2017). The dramatic drop in DFW rates in fall 2016 and spring 2017 (4.35% and 4.1% compared with 13% historically) is followed by a comparative increase in fall 2017 (8.3%).…”
Section: Geosciencesmentioning
confidence: 99%
“…In a recent study looking at factors that foster sense of belonging among managers in social and health-care services, the concept of trust came up as an underlying theme (Lampinen et al, 2018). Additionally, a study examining factors that contributed to sense of belonging for commuter business students found that feeling empowered to contribute helps to develop sense of belonging (Whitten et al, 2017).…”
Section: Trusting Connectionsmentioning
confidence: 99%
“…In classrooms, students gain and apply the skills and competencies needed for future coursework, careers, and civic life; and classroom experiences likely influence program and college persistence. In commuter institutions, like community colleges, classroom‐based experiences are perhaps even more significant because the classroom is the primary venue for students to interface with the institution (e.g., Whitten et al., 2020).…”
Section: Rationale For Committing To Instructional Improvementmentioning
confidence: 99%